The role of reflection in supporting initially resistant teachers’ implementation of targeted reading instruction - Cutrer-Parraga, Elizabeth A.; Miller, Erica Ellsworth (Frontiers in Education, 2022)
One of the roles of reflection is to support teachers in implementing new instructional techniques (Attard, 2012; Daniel et al., 2013; Lambert et al., 2014). Collaborative reflection is a promising tool in addressing reluctance and resistance to implementing instructional techniques. This qualitative study describes how literacy coaches incorporated collaborative reflection with high implementing and initially resistant-low implementing teachers in four rural, low resourced school districts in the southeastern, United States. The findings indicated that as coaches incorporated collaborative reflection, initially resistant-low implementing teachers were more likely to share instructional needs with coaches, feel more confident in implementing the literacy intervention and express less resistance to coaching. Additional research is needed to understand collaborative reflection more fully as an aspect of the coach-teacher relationship.